Framing Pemberitaan BangkaPos.com tentang Razia Tambang Timah Illegal di Propinsi Bangka-Belitung - Eko Tejo Marvianto; Ahmad Toni (Indonesian Scientific Journal (Jurnal Ilmiah Indonesia), 2020)
This research aims to see how the news framing of news portal BangkaPos.com in reporting a crackdown on illegal tin mining in its editions on November 2019 and March 9, 2020. The selection of news portal Bangkapos.com was based on the consideration that it is the only local daily newspaper that consistently reviews and reports the issue. This research uses Zhongdan Pan and Gerald M. Kosicki framing model. This research was conducted through qualitative approaches based on constructivist paradigm. The results of this research suggest that the news framing points to power politics with regard to a physical clash between miners and Public Order Agency (Satpol PP) personnel in Sijuk Village, Belitung Regency.